Study of the Prevalence of Gastrointestinal Diseases Among Conscripts - Kabilova Gulshan Abdirashidovna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Functional gastrointestinal disorders (FGIDs) are increasingly recognized as significant global health burdens, particularly among young adults exposed to high stress, irregular routines, and limited dietary diversity. Specific Background: Military conscripts face unique physical and psychosocial pressures that may exacerbate FGID risks; however, Central Asian populations, including Uzbekistan, remain underrepresented in FGID epidemiology. Knowledge Gap: No prior standardized, large-scale study has assessed FGID prevalence and psychosomatic correlates among Uzbek military personnel, leaving a void in understanding regional patterns and predictors. Aims: This study aimed to determine the prevalence, subtypes, and psychological correlates of FGIDs among Uzbek conscripts using Rome-based diagnostic tools and the SCL-90R scale. Results: Among 910 participants aged 20–25, FGIDs were present in 19.8%, with functional dyspepsia and irritable bowel syndrome predominating. Somatization and obsessive–compulsive traits emerged as independent predictors, while depression showed a weak inverse relationship. Novelty: This is the first systematic study to map FGID prevalence and psychosomatic predictors in Uzbekistan’s conscript population, bridging regional epidemiological gaps. Implications: Findings underscore the necessity of integrating psychological and gastrointestinal screening, stress management, and dietary regulation into military health programs to enhance servicemen’s well-being and operational readiness.Highlight : The study found that FGIDs affected about 19.8% of Uzbek conscripts, mainly functional dyspepsia and irritable bowel syndrome. Somatization and obsessive–compulsive traits were identified as key psychological predictors of FGIDs. It represents the first systematic appraisal in Uzbekistan, highlighting psychosomatic and gut–brain interaction in military settings. Keywords : Functional Gastrointestinal Disorders, Conscripts, Uzbekistan, Somatization, Psychosomatic Factors